Association Between Unintentional Child Injury in the Home and Parental Implementation of Modifications for Safety - Jones, Vanya C. (JAMA Pediatr, 2018)
This study of pediatric emergency department medical records explores children’s unintentional home injuries and parents’ reports of the cause of the injury, what could have prevented it, and changes made in homes afterward.